Increasing the Productivity and Independence of Ex-People with Mental Disorders (ODGJ) Through Life Skills Based Empowerment: Peningkatan Produktivitas dan Kemandirian Ex-Orang Dengan Gangguan Jiwa (ODGJ) Melalui Pemberdayaan Berbasis Life Skill - Cahaya, Noor; Wathan , Nashrul; Kaidah, Siti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
People with mental disorders experience disturbances in thoughts, feelings, and behaviors that cause them to experience decreased productivity and personal autonomy. The program was aimed at increasing the productivity and personal autonomy of ex-ODGJ through life skills-based training in the form of making handicrafts. The target of the program were ex-ODGJs who were undergoing the rehabilitation process at the Rumah Singgah "Baiman" in Banjarmasin. The program was conducted in three stages, survey, implementation, and evaluation. Implementation was conducted in the form of training, which was carried out in 2 meetings. The total number of participants was 20, and they were divided into 4 groups. At the first meeting, we were given an introduction to how to operate a sewing machine and the practice of sewing independently. In the second meeting, participants were asked to independently produce hampers. The conclusion of this program was in the form of a positive impact on ex-ODGJ, which was assessed based on the independence parameter of 75% of participants being able to independently produce handicraft products according to the stages that have been taught; a 100% attendance rate, which describes the participants' motivation to participate in the activity; and based on the results of a qualitative assessment through interviews, information was obtained that participants felt happy and benefited from the program.